2014
DOI: 10.1371/journal.pone.0101249
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Intraepithelial Lymphocyte Cytometric Pattern Is More Accurate than Subepithelial Deposits of Anti-Tissue Transglutaminase IgA for the Diagnosis of Celiac Disease in Lymphocytic Enteritis

Abstract: Background & AimsAn increase in CD3+TCRγδ+ and a decrease in CD3− intraepithelial lymphocytes (IEL) is a characteristic flow cytometric pattern of celiac disease (CD) with atrophy. The aim was to evaluate the usefulness of both CD IEL cytometric pattern and anti-TG2 IgA subepithelial deposit analysis (CD IF pattern) for diagnosing lymphocytic enteritis due to CD.MethodsTwo-hundred and five patients (144 females) who underwent duodenal biopsy for clinical suspicion of CD and positive celiac genetics were prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 39 publications
(84 reference statements)
4
62
0
2
Order By: Relevance
“…21 However, it has been reported that analysis of the intraepithelial intestinal lymphocyte flow cytometric pattern is an accurate method for identifying CD in the initial diagnostic biopsy of seronegative patients presenting with lymphocytic enteritis, and it seems to be better than antiÀtissue transglutaminase 2 intestinal deposits. 22 Therefore, a more accurate evaluation of the duodenal histology, using this method, should be recommended in all NCWS patients that show the DQ2 or the DQ8 haplotypes and duodenal lymphocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, it has been reported that analysis of the intraepithelial intestinal lymphocyte flow cytometric pattern is an accurate method for identifying CD in the initial diagnostic biopsy of seronegative patients presenting with lymphocytic enteritis, and it seems to be better than antiÀtissue transglutaminase 2 intestinal deposits. 22 Therefore, a more accurate evaluation of the duodenal histology, using this method, should be recommended in all NCWS patients that show the DQ2 or the DQ8 haplotypes and duodenal lymphocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…The use of these unified cut‐offs did not change the classification of the intraepithelial lymphocyte pattern in any patient with respect to the previous one. There were four intraepithelial lymphocyte patterns: A normal pattern, an isolated decrease in CD3 − , an isolated increase in TCRγδ + and coeliac lymphogram (an increase in TCRγδ + plus a decrease in CD3 − ).…”
Section: Methodsmentioning
confidence: 99%
“…However, a drawback of this meta‐analysis was the absence of a subgroup of seronegative coeliac disease among cases and a subgroup of sufficient noncoeliac atrophy patients among controls, since these are the patient subgroups for whom TCRγδ + count and coeliac lymphogram have the highest diagnostic relevance. Two of the studies included provided data on a small sample of noncoeliac villous atrophy patients suggesting that TCRγδ + count may be useful to rule out coeliac disease in this setting …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, patients with anti IgATG2 ≥ 100 U/ml show more advanced disease and carry a larger number of CD associated HLA-DQ heterodimers [18]. On the contrary, most recently, a Spanish group, found that intestinal ϒδ+ intraepithelial lymphocyte cytometric pattern is more accurate than subepithelial deposits of anti -IgA-TG2 ABs for CD diagnosis [19]. Anti TG2 autoantibodies expose a lower avidity compared with alloantibodies directed against gliadin, indicating different regulation or site of initiation of these humeral response [20].…”
Section: Anti Tg2 Abs Secretion Binding and Distributionmentioning
confidence: 99%